SISTEM INFORMASI SEBAGAI PEMODERASI PENGARUH KOMPLEKSITAS AUDIT DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT - Deviani, Ni Putu Trisna; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of audit complexity, time budget pressure on audit quality with an understanding of information systems as moderating the public accounting firm in Bali. Data collection method used was a questionnaire with non-probability sampling technique and get 58 samples. Data analysis technique used is multiple linear regression and Moderated Regression Analysis. The results of this study indicate that the complexity of the audit and the time budget pressure negatively affect audit quality. This shows that the higher complexity of the audit and the time budget pressure in the process of auditing the quality of the audit could decrease, in addition to the understanding of the information system is not moderating influence of the complexity of the audit on the quality of the audit, but the understanding of information systems to moderate the influence of time budget pressure on audit quality
Keywords: information systems, the complexity of the audit, time budget pressure and quality audit